Framework for Circular-Economy Based Remanufacturing in Electrical and Electronic Equipment: A Case Study Approach - Abdul Azis; Edwar Ali; Erlita Sulistiati; Rosalina Yani Widiastuti; Abdurrahman Abdurrahman; Suyahman Suyahman (International Forum of Researchers and Lecturers, 2024)
E-waste has become a critical global issue due to the rapid growth of electronic product consumption and the environmental risks associated with improper disposal. Traditional disposal methods, such as landfilling and incineration, are no longer sustainable as they lead to environmental degradation, health hazards, and loss of valuable resources. In contrast, remanufacturing, a key component of the circular economy, offers a more sustainable solution. This study explores the effectiveness of remanufacturing as a strategy for e-waste management, focusing on its ability to reduce waste generation and improve material efficiency in the electronics industry. The research utilizes a case study approach, examining industrial-scale remanufacturing processes, including material input-output analysis to track resource flows and waste streams. The findings reveal a significant reduction in e-waste generation, with up to a 50% decrease in waste volume, and substantial improvements in material recovery, particularly in metals like gold and copper. Additionally, the study highlights the economic and environmental benefits of remanufacturing, such as cost savings and resource conservation. However, the study also identifies barriers to the widespread adoption of remanufacturing, including technological, financial, and regulatory challenges. The results underscore the potential of a circular-economy-based remanufacturing model as a sustainable solution for the electronics industry. The study calls for further research into improving remanufacturing technologies, enhancing policy frameworks, and expanding circular economy practices across various industries.